Role of Spleen Stiffness Measurements with 2D Shear-Wave Elastography for Esophageal Varices in Patients with Compensated Advanced Chronic Liver Disease - Cristina Muzica; Sorina Diaconu; Sebastian Zenovia; Laura Huiban; Carol Stanciu; Horia Minea; Irina Girleanu; Mihaela Muset; Tudor Cuciureanu; Stefan Chiriac; Ana-Maria Singeap; Camelia Cojocariu; et al. (Diagnostics)
Background/Objectives: Esophageal varices (EVs) represent an important portal hypertension complication in patients with compensated advanced chronic liver disease (cACLD). Although upper gastrointestinal endoscopy is currently the gold standard for EV diagnosis, recent guidelines recommend non-invasive approaches to assess EV risk in cACLD patients to reduce unnecessary endoscopies. Our study aims to evaluate spleen stiffness measurement (SSM) using 2D shear-wave elastography (2D-SWE) as a non-invasive predictor of EV presence and severity in patients with cACLD. Methods: We included 73 cACLD patients referred to our liver clinic over one year. SSM and liver stiffness measurement (LSM) were performed using 2D-SWE, with specific cut-off values applied to rule in or rule out clinically significant portal hypertension (CSPH) according to Baveno VII consensus criteria. Upper gastrointestinal endoscopy was performed in all patients to confirm EV presence and grade. Results: Among all patients, 49.3% had no EV, while 50.7% presented with different EV grades (15.1% grade I, 13.7% grade II, 9.6% grade III, and 12.3% grade IV). A strong correlation was observed between elevated SSM values and EV presence, with SSM values > 32.8 kPa highly suggestive of EV (AUROC = 0.95, 95% CI: 0.909–0.995, p < 0.001). SSM values exceeding 40.4 kPa were associated with more advanced EV grades. Combining LSM and SSM improved diagnostic accuracy, effectively stratifying EV risk without invasive procedures. Conclusions: SSM via 2D-SWE is a promising, non-invasive tool for EV prediction in cACLD, aligning with Baveno VII recommendations to minimize unnecessary endoscopies. Further validation is required to refine diagnostic thresholds and expand applicability across different chronic liver disease etiologies.